Factors that affect housing price in Malaysia / Noor Auni Mohd Rosli - Mohd Rosli, Noor Auni (2019)
House prices mostly depends on the location of housing construction Housing Prices in general are influenced by economics fundamentals as well as supply and demand dynamics of the local housing market. Therefore, the purpose of this this is to examine the factor that affect housing price in Malaysia. A set of data were obtained from NAPIC data, World Bank data, DataStream Professional, International Monetary Fund (IMF) data, and Thomson Reuters Eikon from year 1982 until 2017. The regression model that has been used is Ordinary Least Square (OLS) comprising 36 observations. Malaysia housing price index has been used as a dependent variable while interest rate, inflation rate, population and gross domestic product serve as an independent variable for this study. The findings show two independent variables gives positive significant relationship which is interest rate and population. However, the inflation rate has negative insignificant while the gross domestic product has positive insignificant.